2007
DOI: 10.1152/ajpcell.00345.2006
|View full text |Cite
|
Sign up to set email alerts
|

Acute activation of NHE3 by dexamethasone correlates with activation of SGK1 and requires a functional glucocorticoid receptor

Abstract: Glucocorticoids stimulate the intestinal absorption of Na(+) and water partly by regulation of the Na(+)/H(+) exchanger 3 (NHE3). Previous studies have shown both genomic and nongenomic regulation of NHE3 by glucocorticoids. Serum and glucocorticoid-inducible kinase 1 (SGK1) has been shown to be part of this cascade, where phosphorylation of NHE3 by SGK1 initiates the translocation of NHE3 to the cell surface. In the present work, we examined a series of changes in SGK1 and NHE3 induced by glucocorticoids usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 56 publications
(95 reference statements)
7
55
0
1
Order By: Relevance
“…663 has been reported to be a specific phosphorylation site for SGK1 and to be necessary for dexamethasone to stimulate NHE3 over short times, not involving transcriptional regulation (39,40). Because our studies showed that cGMP/cGKII phosphorylation of NHE3 at this site inhibited NHE3 activity, we initially confirmed that dexamethasone stimulates NHE3 activity under basal conditions through phosphorylation of Ser 663 and increases NHE3 surface expression (Fig.…”
Section: Dexamethasone Fails To Stimulate Nhe3 Activity or Increase Ssupporting
confidence: 60%
“…663 has been reported to be a specific phosphorylation site for SGK1 and to be necessary for dexamethasone to stimulate NHE3 over short times, not involving transcriptional regulation (39,40). Because our studies showed that cGMP/cGKII phosphorylation of NHE3 at this site inhibited NHE3 activity, we initially confirmed that dexamethasone stimulates NHE3 activity under basal conditions through phosphorylation of Ser 663 and increases NHE3 surface expression (Fig.…”
Section: Dexamethasone Fails To Stimulate Nhe3 Activity or Increase Ssupporting
confidence: 60%
“…6B) and NHE3 activity (Fig. 6C), consistent with previous studies using Caco-2 or rabbit intestinal brush-border membrane (35,42).…”
Section: Sk-co15 Cells Endogenously Express Nhe1 Nhe2 and Nhe3supporting
confidence: 91%
“…The characterization of NHE3 has utilized several cell lines, including fibroblasts, OK, Caco-2, and, to a lesser extent, IEC-6 cells (16,18,35,40,43). Of these, the OK cell line shows robust expression of NHE3, but its renal proximal tubule origin limits its application in the study of intestinal NHEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They directly stimulate NHE3 through both acute and chronic mechanisms (Bobulescu and Moe 2009). The acute effect of glucocorticoids on cell surface NHE3 is mediated by the activation of HNE3 exocytosis (Bobulescu et al 2005) and a glucocorticoid receptor-dependent mechanism that activates serum and glucocorticoid-inducible kinase1 (SGK1) in a nongenomic manner (Wang et al 2007). Glucocorticoids have also been found to enhance the function of insulin in stimulating NHE3 activity (Klisic et al 2002).…”
Section: Glucocorticoidsmentioning
confidence: 99%